PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA BANK SYARIAH INDONESIA KC PALEMBANG - Febriani Ami Susanti; Ulil Amri (CV. Cendikiawan Muda Sriwijaya, 2024)
The purpose of this research to obtain the empirical evidence regarding the effect of work motivation and career development on work productivity for employees at Palembang Branch Office of Bank Syariah Indonesia.Productivity is very important for employees in the company. With work productivity, it is hoped that work will be carried out efficiently and effectively to achieve the stated goal. The type of research used is quantitative research. The population in this study were all employees of Palembang Branch Office of Bank Syariah Indonesia and the sample was chosen for this research are 30 employees. The data used are primary and secondary data. Data collection techniques using questionnaires. The analytical method used is descriptive analysis method and quantitative analysis, namely multiple linear regression analysis. Based on partial testing, work motivation and career development influence employee work productivity. This can be seen from the work motivation variable which has a t-value = 0.857 which is smaller than the t-table = 1.705. Meanwhile, career development has a calculated t-value = 1.840 which is greater than t-table = 1.705. and based on the coefficient of determination (R2) value of 0.199, this means that work motivation and career development can explain its influence on employee work productivity, namely 19.9% and the remaining 80.1% can be explained by other variables not included in this research.